PROMOTING CULTURAL AWARENESS THROUGH INTERCULTURAL LISTENING ACTIVITIES - Arini Nurul Hidayati; Santiana Santiana (JURNAL TAHURI, 2020)
As diversity is one of heated issues emerging in English teaching learning circumstance in Indonesia, teachers have to initiate strategies to restrain the probability of fragment among the students which can furthermost impact on their ability to communicate among cultures. Intercultural listening activities conducted at a university in West Java has evidently proven its contribution in consolidating the students’ cultural awareness. Through reflective journals and focused-group interviews, it is found that the students are able to discover, understand, and compare their own culture and others, realize the similarities and differences, and respect the existing gaps in between. Thus, they are presumed to be more ready to take part in the intercultural communication